Sphingolipids and Plant Defense/Disease: The “Death” Connection and Beyond - Berkey, Robert; Bendigeri, Dipti; Xiao, Shunyuan (Frontiers in Plant Science, 2012)
Sphingolipids comprise a major class of structural materials and lipid signaling molecules in all eukaryotic cells. Over the past two decades, there has been a phenomenal growth in the study of sphingolipids (i.e. sphingobiology) at an average rate of >1000 research articles per year. Sphingolipid studies in plants, though accounting for only a small fraction (~6%) of the total number of publications, have also enjoyed proportionally rapid growth in the past decade. Concomitant with the growth of sphingobiology, there has also been tremendous progress in our understanding of the molecular mechanisms of plant innate immunity. In this review, we (i) cross examine and analyze the major findings that establish and strengthen the intimate connections between sphingolipid metabolism and plant programmed cell death (PCD) associated with plant defense or disease; (ii) highlight and compare key bioactive sphingolipids involved in the regulation of plant PCD and possibly defense; (iii) discuss the potential role of sphingolipids in polarized membrane/protein trafficking and formation of lipid rafts as subdomains of cell membranes in relation to plant defense; and (iv) where possible, attempt to identify potential parallels for immunity-related mechanisms involving sphingolipids across kingdoms.